Cyclical and Value-Based Quality Assurance: A Case Study of a Religious Program at an Islamic Senior High School in Indonesia - Jannana, Nora Saiva; Sugiyono, Sugiyono; Wijayanti, Wiwik (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2025)
This study examines how an Islamic senior high school in Indonesia implements a cyclical, participatory quality assurance (QA) model to strengthen educational outcomes. It addresses the need for context-responsive QA systems in faith-based institutions, where religious values and global standards must be harmonized. Employing a qualitative case study design, the research draws upon interviews, observations, and document analysis involving school leaders, teachers, and students at MAPK MAN 1 Surakarta. Data were examined through thematic analysis to uncover institutional strategies and stakeholder interactions in QA implementation. Ethical approval was obtained, and reflexivity was maintained to ensure trustworthiness. The findings highlight a five-phase QA cycle that includes mapping, planning, implementation, evaluation, and renewal. These processes are rooted in theological values while incorporating student participation. Several institutional mechanisms, such as digital dashboards, student surveys, electronic report cards, and curriculum review forums, contributed to strengthening graduate achievements in university admissions, academic competitions, and bilingual proficiency. The participatory approach cultivated shared accountability among stakeholders, fostering a culture of quality that integrates spiritual formation with academic excellence. This research presents a contextually grounded model of quality assurance for Islamic education. It enhances the traditional PDCA cycle by embedding moral and spiritual accountability and inclusive governance. The study advances discourse on integrating religious principles into QA frameworks while addressing contemporary educational standards and diverse stakeholder expectations. Although the findings are specific to one Islamic senior high school in Java, the model provides valuable insights for other faith-based institutions seeking to build participatory and value-oriented QA systems in resource-limited contexts.